PHANEROZOIC TECTONIC EVOLUTION OF THE CIRCUM-NORTH PACIFIC - Nokleberg W.J.; Scholl D.W.; Parfenov L.M.; Monger J.W.H.; Norton I.O.; Khanchuk A.I.; Stone D.B.; Scotese C.R.; Fujita K. (My University, 2001)
2000.08 Phanerozoic tectonic evolution of the Circum-North Pacific Author: Nokleberg, Warren J; Parfenov, Leonid M; Monger, James W H; Norton, Ian O; Khanchuk, Alexander I; Stone, David B; Scotese, Christopher R; Scholl, David W; Fujita, Kazuya Abstract: The Phanerozoic tectonic evolution of the Circum-North Pacific is recorded mainly in the orogenic collages of the mountain belts that separate the North Pacific from the eastern North Asian and western North American cratons. The geologic history of the terranes and overlap assemblages that constitute these orogenic collages is highly complex because of post-accretion dismemberment and translation during strike-slip faulting that occurred subparallel to the continental margins.